2016
DOI: 10.1016/j.ejmp.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of operator position, height and body orientation on eye lens dose in interventional radiology and cardiology: Monte Carlo simulations versus realistic clinical measurements

Abstract: Simple precautions, such as the positioning of the image screen away from the X-ray source, lead to a significant reduction of the eye lens dose. Measurements and simulations performed in this work also show that a general eye lens correction factor of 0.5 can be used when lead glasses are worn regardless of operator position, height and body orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Based on the MIRD phantom, the project Optimization of Radiation Protection for Medical Staff (ORAMED) conducted a simulation campaign to investigate various parameters that contribute to eye lens dose in IR . Koukorava and Principi also examined similar parameters using the MIRD phantom . However, phantoms used in these studies are not able to accurately represent the anatomical structure of the human body, especially small features such as the eye lens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the MIRD phantom, the project Optimization of Radiation Protection for Medical Staff (ORAMED) conducted a simulation campaign to investigate various parameters that contribute to eye lens dose in IR . Koukorava and Principi also examined similar parameters using the MIRD phantom . However, phantoms used in these studies are not able to accurately represent the anatomical structure of the human body, especially small features such as the eye lens.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Koukorava and Principi also examined similar parameters using the MIRD phantom. 16,17 However, phantoms used in these studies are not able to accurately represent the anatomical structure of the human body, especially small features such as the eye lens. The commonly used MIRD phantom is a stylized phantom based on quadratic equations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that staff height may also influence occupational dose as the taller the staff member is, the further away their head is from the source of scattered radiation (Principi et al, ). This study did not find a significant correlation between the heights of nursing staff and head dose which reflects the findings by Antic et al, (), but contradicts clinical and phantom studies which found that dosimeters worn at chest level detected higher levels of radiation in short staff members than in their taller colleagues (Omar, Marteinsdottir, Kadesjo, & Fransson, ; Rigatelli et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that staff height may also influence occupational dose as the taller the staff member is, the further away their head is from the source of scattered radiation (Principi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that at this position the clinician will be exposed to the least amount of radiation, due to a shielding effect caused by the flat panel detector. 20 The height of the head phantom was 168.5 cm, determined by the mean average height of both a male and female British person. 21 Accumulated dose rates to the clinician's eye lenses from five 10-second exposures at 75 kV 25.2 mAs with a focal spot size of 1 mm and a tantalum filter were recorded for different angles of gaze to decrease random error, therefore promoting higher levels of accuracy.…”
Section: Methodsmentioning
confidence: 99%